2015
DOI: 10.1007/s11738-015-1814-y
|View full text |Cite
|
Sign up to set email alerts
|

Lithium distinguishes between growth and circumnutation and augments glutamate-induced excitation of Helianthus annuus seedlings

Abstract: An effect of lithium (Li ? ) on growth, circumnutation, and glutamate-induced excitation in sunflower (Helianthus annuus L.) seedlings was investigated using time-lapse photography and extracellular electrical potential measurements. The seedlings were treated with a micro and millimolar concentration of lithium chloride (LiCl) both persistently in a hydroponic medium and acutely through Li ? injection. The length of hypocotyls, fresh weight of seedlings, intensity and period of circumnutation, and the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This confirms a strong resistance of the CN period to osmotic and salt stress (Erdei et al, 1998 ). The independence of the CN period of the growth of hypocotyls confirmed some degree of independence between growth and CN behavior, as in the case of lithium treatment (Stolarz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…This confirms a strong resistance of the CN period to osmotic and salt stress (Erdei et al, 1998 ). The independence of the CN period of the growth of hypocotyls confirmed some degree of independence between growth and CN behavior, as in the case of lithium treatment (Stolarz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 56%
“…Glutamate is a major amino acid involved both in nitrogen metabolism and in nitrogen signaling (Forde and Lea, 2007 ; Mousavi et al, 2013 ). Previously, we showed that lithium modulated Glu-induced excitability and CN in sunflower seedlings (Stolarz et al, 2015 ). Thus, we expected that also the external concentration of K, Na, and Cl could modulate the Glu-induced series of APs.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations